2009
DOI: 10.1111/j.1420-9101.2009.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Females benefit from multiple mating but not multiple mates in the burying beetle Nicrophorus vespilloides

Abstract: Male reproductive success generally increases with number of mates but this need not be true for females. If females are the limiting sex, as few as one mate can be optimal. Despite the theoretical differences driving multiple mating in the sexes, multiple mating is the norm rather than the exception. Empirical investigations are therefore required to determine why females mate with multiple males. Both nonadaptive (correlated responses to selection on males, given the mean mating rates have to be the same) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Nevertheless, we anticipate that the microsatellites we have developed will prove most useful in future work for assigning parentage (S Pascoal, 2016, unpublished data) because the large brood size typically seen in N. vespilloides still makes other techniques prohibitively expensive. N. vespilloides mates rampantly and promiscuously in the laboratory (e.g., House et al, 2009) and in natural populations (e.g., Müller et al, 2007). Although several previous studies have analysed strategies used by males for securing paternity (e.g., Eggert, 1992; House et al, 2009), parentage has never before been assigned using microsatellites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we anticipate that the microsatellites we have developed will prove most useful in future work for assigning parentage (S Pascoal, 2016, unpublished data) because the large brood size typically seen in N. vespilloides still makes other techniques prohibitively expensive. N. vespilloides mates rampantly and promiscuously in the laboratory (e.g., House et al, 2009) and in natural populations (e.g., Müller et al, 2007). Although several previous studies have analysed strategies used by males for securing paternity (e.g., Eggert, 1992; House et al, 2009), parentage has never before been assigned using microsatellites.…”
Section: Discussionmentioning
confidence: 99%
“…N. vespilloides mates rampantly and promiscuously in the laboratory (e.g., House et al, 2009) and in natural populations (e.g., Müller et al, 2007). Although several previous studies have analysed strategies used by males for securing paternity (e.g., Eggert, 1992; House et al, 2009), parentage has never before been assigned using microsatellites. The microsatellites we have developed here thus pave the way for more detailed analyses of the evolutionary causes and consequences of promiscuity in this species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mating with multiple males has been shown to be beneficial to females in echinoderms (Evans and Marshall 2005), insects (Tregenza and Wedell 1998;Fedorka and Mousseau 2002;Dunn et al 2005), fishes (Evans and Magurran 2000) and reptiles (LaDage et al 2008), but it can also be associated with a reduction of the female's reproductive output, as reported for many insect species (e.g., Orsetti and Rutowski 2003;Bybee et al 2005;Ronkainen et al 2010). At the same time, several studies found no effect of polyandry on female fecundity in insects (e.g., Baker et al 2001;Schwartz and Peterson 2006;House et al 2009). …”
Section: Introductionmentioning
confidence: 86%
“…In the vast majority of tested species, females mated in nature produce offspring sired by more than one male. Polyandry is common in wild Drosophila, 1 - 17 but also in crickets, 18 burying beetles 19 and other insects, 20 as well as birds 21 and mammals 22 , 23 . Compared with birds, in which studies of hundreds of species in the wild demonstrate the ecological correlates of genetic polyandry, generalities about Drosophila polyandry come mostly from laboratory studies, and most generalities about Drosophila polyandry come from only two species, D. melanogaster and D. pseudoobscura , though this is changing as more behavioral and evolutionary ecologists 24 ask questions about non-model Drosophila and Drosophila species in nature.…”
Section: Multiple Mating In Drosophilamentioning
confidence: 99%